Theranostic Radioembolization: Radiation Dosimetry-Guided Treatment Planning and Delivery - Bailey, Dale L.; Bernard, Elizabeth J.; Maher, Richard; Goh, Albert C.; Gholami, Yaser H.; Pavlakis, Nick; Willowson, Kathy P. (World Journal of Nuclear Medicine, 2025)
Radioembolizaton of hepatic malignancy is an accepted palliative treatment option in many subjects. The process of working up an individual for a radioembolization procedure permits pretreatment radiation dosimetry to be estimated, which is not possible with many other theranostic pairs of radionuclides. These estimates can then be used to prescribe the desired amount of radionuclide therapy (RNT), in radiation dose units of gray (Gy), to treat the cancer tissues to a desired level as well as permitting the radiation dose to the normal liver compartment to be minimized. As such, radioembolization represents an excellent example of a theranostic approach to treatment where individualization of the therapy can be highly tailored. The necessary tools are now available to implement this approach on a wider scale, which should improve outcomes for the treated individuals. The aim of this review article was to present a contemporary approach to personalized treatment planning for radioembolization and to emphasize the theranostic aspects of the process. A clinical case is presented demonstrating the potential for excellent clinical outcomes using an image-based and informed treatment plan developed by the multidisciplinary team of nuclear physicians, interventional radiologists, medical oncologists, and medical physicists.
Keywords: radioembolization; theranostic; hepatic malignancy; SIRT; liver-directed therapy